Synthesis of silver nanoparticles using oxidized amylose and combination with curcumin for enhanced antibacterial activity. (15th February 2020) - Lyu, Yongbo; Yu, Mengchao; Liu, Qisong; Zhang, Qingmei; Liu, Zhanhong; Tian, Ye; Li, Defu; Changdao, Mu
Highlights: Hybrid antibacterial agent was developed based on silver nanoparticles and curcumin. Silver nanoparticles were synthesized using oxidized amylose as reducing agent. Solubility of curcumin was increased by encapsulating into oxidized amylose. The hybrid antibacterial agent exhibited enhanced antibacterial activity. The hybrid presented good antioxidant activity and cell compatibility. Abstract: Many kinds of multi-drug-resistant microorganisms have appeared. Moreover, monotherapy is increasingly no longer adequate for many complicated bacterial infections. Therefore, development of efficient combination antibacterial agent is becoming crucial. Herein, we present a hybrid antibacterial agent with enhanced antibacterial activity and high aqueous dissolubility based on silver nanoparticles and curcumin. The silver nanoparticles were firstly synthesized using oxidized amylose as an environmentally friendly reducing agent and stabilizer. Then, curcumin was added into the above mixture to get the hybrid antibacterial agent. The hybrid antibacterial agent presented high dissolubility in aqueous solution and enhanced antibacterial activity. In addition, the hybrid antibacterial agent presented good antioxidant activity and cell compatibility. Overall, the developed hybrid antibacterial agent has a potential to combat multiple bacteria-induced infections of wound surfaces.